2007
DOI: 10.1152/ajpendo.00024.2007
|View full text |Cite
|
Sign up to set email alerts
|

Telmisartan prevents the glitazone-induced weight gain without interfering with its insulin-sensitizing properties

Abstract: Glitazones are peroxisome proliferator-activated receptor (PPAR)-gamma agonists with powerful insulin-sensitizing properties. They promote the development of metabolically active adipocytes that can lead to a substantial gain in fat mass. Telmisartan is an ANG II type 1 receptor antagonist with partial PPAR-gamma agonistic properties. Recently, telmisartan has been reported to prevent weight gain and improve insulin sensitivity in diet-induced obese rodents. The goal of this study was to examine the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
1
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 18 publications
6
29
1
1
Order By: Relevance
“…As analogous data in an animal experiment, Araki (11,13,14). Different from thiazolidinediones, telmisartan does not induce obesity (13).…”
Section: T a B L E 1 I N S U L I N S E C R E T O R Y F U N C T I O Nsupporting
confidence: 56%
See 1 more Smart Citation
“…As analogous data in an animal experiment, Araki (11,13,14). Different from thiazolidinediones, telmisartan does not induce obesity (13).…”
Section: T a B L E 1 I N S U L I N S E C R E T O R Y F U N C T I O Nsupporting
confidence: 56%
“…Different from thiazolidinediones, telmisartan does not induce obesity (13). Sugimoto et al (14) (17,18).…”
Section: T a B L E 1 I N S U L I N S E C R E T O R Y F U N C T I O Nmentioning
confidence: 99%
“…This effect was specifically tested in a recent study that investigated the effect of telmisartan on glitazone-induced weight gain in two models of obesity. 20 They showed that both obese Zucker rats and high-fat fed Sprague-Dawley rats gained more weight when treated with the PPAR-agonist pioglitazone, and that the increases in abdominal and total body fat were substantially decreased by concomitant treatment with telmisartan. This effect of telmisartan was mediated by reduced food intake as pair-fed animals showed a similar reduction in fat mass as animals treated with both pioglitazone and telmisartan.…”
Section: Mechanisms Underlying the Reduction In Fat Massmentioning
confidence: 99%
“…In general, studies in rats showed that blockade of the RAS with an AT 1 receptor antagonist reduces body weight gain and visceral or epididymal fat mass. [19][20][21] This effect is usually accompanied by a reduction in food intake, and some studies also suggest that increases in fatty acid metabolism or energy expenditure might be part of the mechanism. However, some AT 1 receptor antagonists were more effective than others, 21 and this difference was attributed to the additional property of some drugs in this class, which are partial agonists at peroxisome proliferator-activated receptor (PPAR)-g. 22 In humans, trials of AT 1 receptor antagonists with low numbers of subjects did not produced significant weight loss, 18,23 but one study reported a significant reduction in visceral fat.…”
Section: Introductionmentioning
confidence: 99%
“…Many putative pharmaceutical agents induce reduced food intake (8,9,36,44), leading to uncertainty as to whether the effects seen were due to direct pharmacological actions of the drugs or were simply secondary effects related to anorexia. A common approach to this problem has been to include control (non-drug-treated) animals in the experimental design that are on a daily basis provided with a single portion of food equal to that consumed by drug-treated animals (so-called pair feeding) (29,57). However, in the course of a pharmaceutical study, in which one of the agents had no effect on food intake, we observed that the pair-fed rats showed significant differences in metabolism and pathophysiology compared with the freely fed control animals.…”
mentioning
confidence: 99%